2017
DOI: 10.1002/anie.201708212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polyethylene Glycol Unit on Palladium‐ and Nickel‐Catalyzed Ethylene Polymerization and Copolymerization

Abstract: The transition-metal-catalyzed copolymerization of olefins with polar functionalized co-monomers represents a major challenge in the field of olefin polymerization. It is extremely difficult to simultaneously achieve improvements in catalytic activity, polar monomer incorporation, and copolymer molecular weight through ligand modifications. Herein we introduce a polyethylene glycol unit to some phosphine-sulfonate palladium and nickel catalysts, and its influence on ethylene polymerization and copolymerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 84 publications
1
77
0
1
Order By: Relevance
“…60b Recent examples after 2015 include nickel complexes bearing phosphine sulfonate, 82,83 IzQO, 84 and phosphinearenolate 85 ligands.…”
Section: 7576mentioning
confidence: 99%
“…60b Recent examples after 2015 include nickel complexes bearing phosphine sulfonate, 82,83 IzQO, 84 and phosphinearenolate 85 ligands.…”
Section: 7576mentioning
confidence: 99%
“…[15] Metal-mediated olefin copolymerizations with AA are highly challenging due to the poisoning effect of both the oxygen atom and the carboxylic acid moiety. [22] Angewandte Chemie Zuschriften monomer incorporation ratios,copolymer molecular weights, and copolymer melting points increased concurrently in the order: Pd-O1 < Pd-O2 < Pd-O3.S imilar with the E-MA copolymerization results, Pd-C3 afforded copolymer with the lowest AA incorporation ratio ( Table 2, entry 7), which is proposed to be due to steric effect. Hydrogen atoms have been omitted for clarity.T hermale llipsoids are set at 30 %p robability.…”
mentioning
confidence: 65%
“…Thea bove-mentioned trends were maintained during ethylene (E) copolymerizations with methyl acrylate (MA) and butyl vinyl ether (Table 1, entries [13][14][15][16][17][18][19][20][21][22]. In these copolymerization reactions,the catalytic activities,copolymer molecular weights,c o-monomer incorporation ratios,a nd copolymer melting temperatures follow the order: Pd-O3 > Pd-O2 > Pd-O1.I nc ontrast, Pd-C3 with long alkyl chain afforded polymers with high molecular weights but much lower MA incorporation ratios (Table 1, entries 4, 16, and 20).…”
mentioning
confidence: 97%
“…Significantly, Mecking and co-workers reported insertion copolymerization of ethylene with vinyl chloride using phosphine-sulfonate palladium catalysts,y ielding chlorine-containing copolymers. [58] This beneficial effect is most significant in ethylene copolymerization with polar monomers bearing hydrogen-bond-donating abilities. [54] Mecking and co-workers showed that utilization of some nonconjugated divinyl comonomers can promote chain propagation and suppress b-hydride elimination, thereby increasing copolymer molecular weights (Scheme 3a).…”
Section: Developments Using the Brookhart And Drent Catalystsmentioning
confidence: 99%